1996
DOI: 10.1080/15235882.1996.10668621
|View full text |Cite
|
Sign up to set email alerts
|

Naturalistic Language Assessment of LEP Students in Classroom Interactions

Abstract: The purpose of this study was to assess language competence of second language learners through observing natural interactions in transitional bilingual classrooms. We first developed an instrument in accordance with current second language acquisition theory, and obtained inter-rater reliability on observation categories. We then piloted the instrument in six Grade 5 bilingual classrooms, targeting the social language of 24 individual students. Each student was observed for a total of 12 hours, during twenty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Focused observations enhance the effectiveness of individual conferences, whether conducted within the classroom environment, such as during cooperative learning groups, or beyond the class setting, such as in the school courtyard. To that end, Gomez et al (1996) devised an observational tool tailored for evaluating learners' communication skills in authentic language contexts. This instrument emphasizes seven key language abilities: comprehensibility to others; furnishing essential information for the listener; minimal hesitations; eagerness to engage in conversations; spontaneous utterances; precision (in grammar; usage; and vocabulary); and the development of topics.…”
Section: Innovative Oral Exercises and Assessment Approachesmentioning
confidence: 99%
“…Focused observations enhance the effectiveness of individual conferences, whether conducted within the classroom environment, such as during cooperative learning groups, or beyond the class setting, such as in the school courtyard. To that end, Gomez et al (1996) devised an observational tool tailored for evaluating learners' communication skills in authentic language contexts. This instrument emphasizes seven key language abilities: comprehensibility to others; furnishing essential information for the listener; minimal hesitations; eagerness to engage in conversations; spontaneous utterances; precision (in grammar; usage; and vocabulary); and the development of topics.…”
Section: Innovative Oral Exercises and Assessment Approachesmentioning
confidence: 99%
“…Contrary to the isolated grammar exercises often used in writing instruction for bi/multilingual students, research has shown that bi/multilingual children's growth as writers is best supported by meaning‐based pedagogies and language instruction contextualized within authentic communicative activities (Brisk, 2021; Dutro et al., 2016; Schleppegrell, 2004). We have compelling evidence that bi/multilingual students’ writing development advances when instruction is explicit and structured, compared to unstructured free writing (Gomez et al, 1996; Shanahan & Beck, 2006). Examples of meaning‐based, structured writing instruction include (1) making explicit the purpose of writing and the organizational structures that help realize that purpose; (2) building bi/multilingual students’ language resources to expand their choices in expressing ideas, connecting with their audience, and creating cohesive texts; (3) illustrating how and why texts are similarly or differently organized across languages; and (4) modeling how language‐specific features function to make meaning (Brisk, 2021).…”
Section: Introductionmentioning
confidence: 99%